Implementation of Fiqh Muamalah Principles in the Financing System of Bank Muamalat Indonesia - Wizda Salsabila Harahap (Sufiya Journal of Islamic Studies, 2025)
Compliance with the principles of fiqh muamalah serves as the fundamental pillar in maintaining the integrity of the Islamic banking system in Indonesia. In this context, Bank Muamalat Indonesia stands as a significant representation of how Sharia values are implemented within the framework of modern economic practice. This study provides an in-depth examination of the application of Sharia principles in the financing mechanisms of Bank Muamalat KCP Medan Baru, with a particular focus on murabahah and wakalah contracts. Using a qualitative approach and in-depth interviews with bank officials, the study found that all stages of the financing process—from application submission, identity verification, and feasibility analysis based on the 5C principle, to the execution of contracts—are conducted in accordance with the Fatwa of the National Sharia Council–Indonesian Ulema Council (DSN–MUI) and the Islamic Banking Law. The Sharia Supervisory Board (DPS) plays a crucial role in ensuring that all transactions remain free from elements of riba, gharar, and maisir. The findings reveal that the murabahah financing practices at Bank Muamalat are not merely driven by economic gain but are also deeply rooted in the fulfillment of Islamic ethical values and social justice.